2017
DOI: 10.1017/laq.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Obsidian Sub-Sources at the Zaragoza-Oyameles Quarry in Puebla, Mexico: Similarities With Altotonga and Their Distribution Throughout Mesoamerica

Abstract: We present data produced through archaeological and geological survey, as well as geochemical analysis of the Zaragoza-Oyameles obsidian source area located on the northern and western flanks of the Los Humeros Caldera in eastern Puebla, Mexico. One result of the intensive archaeological surface survey of this obsidian source area was the identification of 117 obsidian flow-band exposures. Geologic samples from 40 of these were submitted for instrumental neutron activation analysis. Eighty-five projectile poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Although Oyameles group has a higher density, this grouping may well be subdivided into two or three possible subsources. The result is consistent with the analysis performed by reference [77], who identified three sub-sources known as Z-O1, Potreros Caldera and Gomez Sur.…”
Section: Discussionsupporting
confidence: 91%
“…Although Oyameles group has a higher density, this grouping may well be subdivided into two or three possible subsources. The result is consistent with the analysis performed by reference [77], who identified three sub-sources known as Z-O1, Potreros Caldera and Gomez Sur.…”
Section: Discussionsupporting
confidence: 91%
“…) and Zaragoza‐Oyameles (Knight et al . ). A recent study of geological samples from Paredón suggested spatial variability in its geochemistry (Millhauser et al .…”
Section: Introductionmentioning
confidence: 97%
“…Some source areas host deposits of obsidian with multiple geochemical signatures, reflecting complex histories of eruption and the geochemical evolution of magma chambers between eruptive events (e.g. Ericson & Glascock, 2004;Brown, Reid, & Negash, 2009;Morgan et al, 2009;Poupeau et al, 2010;Glascock, 2011;Argote-Espino et al, 2012;Knight et al, 2017). Obsidian from Glass Buttes in central Oregon, for example, can be assigned to as many as nine geochemical source groups, all found within a 200 km 2 area (Ambroz, Glascock, and Skinner 2001;Frahm 2014;Frahm and Feinberg 2015).…”
Section: What Is An Obsidian "Source"?mentioning
confidence: 99%